Perception of Marital Quality among Young Married Couples in Selangor - Zakaria, Siti Marziah (International Journal of Psychosocial Rehabilitation, 2020)
The divorce rate in Malaysia is on the rise due to deterioration in the quality of marriage among young married couples. The objective of this study is to explore perceptions of marital quality among young married couples in Selangor. This qualitative study uses the phenomenological approach with the involvement of 11 informants who have been married from one (1) to ten (10) years. They are selected through the purposive sampling method. The semi-structured interview method is used in the data collection process. Data are analyzed using the thematic analysis. Results of the study show five (5) key themes to describe the quality of marriage: tolerance, mutual understanding, complementary, sense of respect, and life management as derived from the data. Themes found are fundamental to the building of a strong marriage. The findings of this study can meet the needs of related parties such as the Islamic Development Department of Malaysia (JAKIM) to further strengthen modules for pre- and post-marriage courses. Findings can also be used by the Ministry of Women, Family and Community Development in devising an action plan to improve the quality of marriage for young married couples in Malaysia. This study can also help counsellors in developing appropriate interventions that could help young married couples. Findings can be used as inputs for comprehensive plans and solutions that may indirectly contribute to reducing the divorce rate in Malaysia.